The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/mpg.0b013e3182065cad
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pancreatitis Preceding the Diagnosis of Inflammatory Bowel Disease Is More Frequent in Pediatric Patients

Abstract: IBD presenting as AP was more frequent among the pediatric population with IBD in comparison to adults. It was more common in patients with colitis than in those with ileal disease, suggesting that patients with idiopathic AP should be observed carefully for a possible diagnosis of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 32 publications
6
46
0
3
Order By: Relevance
“…The relationship between IBD and autoimmune pancreatitis (AIP) is mainly confined to UC[13,14]. Several studies have reported positive associations between risk for acute pancreatitis and IBD severity[15-17]. To our knowledge, however, no study has evaluated the clinical course of UC patients who develop pancreatitis according to its etiology.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between IBD and autoimmune pancreatitis (AIP) is mainly confined to UC[13,14]. Several studies have reported positive associations between risk for acute pancreatitis and IBD severity[15-17]. To our knowledge, however, no study has evaluated the clinical course of UC patients who develop pancreatitis according to its etiology.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Our patient's case is unique in that the diagnosis of Crohn's disease came after multiple bouts of pancreatitis, circumstances reported in only a few other cases. 8,9 To our knowledge, this is also the first reported case of pancreatic panniculitis coinciding with pancreatitis and Crohn's disease.…”
Section: Diagnosismentioning
confidence: 82%
“…Pancreatitis without an obvious cause has been diagnosed in patients with Crohn's disease, though an explanation for this relationship has yet to be identified. [4][5][6][7][8][9][10][11][12] The inflammatory process triggered in the walls of the proposed mechanism for this concurrence is that reflux of duodenal contents into the pancreatic duct activates zymogens. 7,10 Then again, as with our patient, pancreatitis also exists without duodenal involvement.…”
Section: Diagnosismentioning
confidence: 99%
“…A multifactorial pathogenesis is recognized, but in some patients idiopathic forms may occur before the onset of IBD. [13] In children, idiopathic chronic pancreatitis occur ten months before the diagnosis of CD with a severe phenotype. [14] Clinical and biological surveys have shown that 20%-30% of patients with pancreatitis remain unknown or idiopathic (Table 1).…”
Section: Introductionmentioning
confidence: 99%